Two-factor authentication for trusted third party free dispersed storage - Esiner, Ertem (2019)
We propose a trusted third party free protocol for secure (in terms of content access, manipulation, and confidentiality) data storage and multi-user collaboration over an infrastructure of untrusted storage servers. It is achieved by the application of data dispersal, encryption as well as two-factor (knowledge and possession) based authentication and access control techniques so that unauthorized parties (attackers) or a small set of colluding servers cannot gain access to the stored data. The protocol design takes into account usability issues as opposed to the closest prior work Esiner and Datta (2016). We explore the security implications of the proposed model with event tree analysis and report on experiment results to demonstrate the practicality of the approach concerning computational overheads. Given that the protocol does not rely on any trusted third party, and most operations including actual collaboration do not require users to be online simultaneously, it is suitable not only for traditional multi-cloud setups but also for edge/fog computing environments.